Closing Editorial: Advancements in Artificial Intelligence for Dentomaxillofacial Radiology—Current Trends and Future Directions - Orhan, Kaan; Costa, Andre Luiz Ferreira; de Castro Lopes, Sérgio Lúcio Pereira [UNESP] (MDPI, 2025)
Artificial intelligence (AI) continues to redefine diagnostic approaches across medical disciplines, and its impact on dentomaxillofacial radiology has increased exponentially in recent years [...].